Design and Evaluation of Short Bovine Lactoferrin-Derived Antimicrobial Peptides against Multidrug-Resistant Enterococcus faecium - Biswajit Mishra; LewisOscar Felix; Anindya Basu; Sai Sundeep Kollala; Yashpal Singh Chhonker; Narchonai Ganesan; Daryl J. Murry; Eleftherios Mylonakis (MDPI AG, 2022)
Enterococcus faecium has become an important drug-resistant nosocomial pathogen because of widespread antibiotic abuse. We developed short and chemically simple antimicrobial peptides (AMPs) with a selective amino acid composition, fixed charge, and hydrophobicity ratio based on the core antimicrobial motif of bovine lactoferrin (LfcinB6). Among these peptides, 5L and 6L (both 12 residues long) demonstrated a narrow spectrum and high antibacterial activity against drug-resistant E. faecium isolates with a minimal inhibitory concentration (MIC) that ranged from 4-16 µg/mL. At 32 µg/mL, peptides 5L and 6L inhibited E. faecium strain C68 biofilm formation by 90% and disrupted established biofilms by 75%. At 40 µg/mL, 5L reduced 1 × 107E. faecium persister cells by 3 logs within 120 min of exposure, whereas 6L eliminated all persister cells within 60 min. At 0.5× MIC, 5L and 6L significantly downregulated the expression of a crucial biofilm gene ace by 8 folds (p = 0.02) and 4 folds (p = 0.01), respectively. At 32 µg/mL, peptides 5L and 6L both depolarized the E. faecium membrane, increased fluidity, and eventually ruptured the membrane. Physiologically, 5L (at 8 µg/mL) altered the tricarboxylic acid cycle, glutathione, and purine metabolism. Interestingly, in an ex vivo model of porcine skin infection, compared to no treatment, 5L (at 10× MIC) effectively eliminated all 1 × 106 exponential (p = 0.0045) and persister E. faecium cells (p = 0.0002). In conclusion, the study outlines a roadmap for developing narrow-spectrum selective AMPs and presents peptide 5L as a potential therapeutic candidate to be explored against E. faecium.